(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Fairy tales, with their vivid imagery and fascinating plots, help children learn basic sociocultural values such as friendship, honesty, kindness, justice and respect for others. Through interaction with the characters and their experiences, children learn practical ways to solve social conflicts and understand the emotions of others.